Health Expenditure Dynamics in Türkiye for The Years 1999-2024 and Their Implications for The Health System - Abay, Perihan; Yücel, Ali Serdar; Korkmaz, Murat; Özdayı, Nahit; Kuyucu, Mihalis (michael) (Balıkesir Üniversitesi, 2026)
Objective: The aim of the study is to identify the components of health expenditures in Türkiye and their effects on total health expenditures and to examine the effects of health expenditures on access to health services. Materials and Methods: In this study, health expenditures in Türkiye were analyzed by using data from the Turkish Statistical Institute (TurkStat) for the period 1999-2024. The analyses were conducted with E-Views 12.0 program and included Unit Root Test, Granger Causality and Regression analyses. Results: The results of the study revealed the effects of different components of health expenditures on total health expenditures. Current health expenditures, hospital expenditures and other medical equipment expenditures have significant effects on total health expenditures. In addition, the effects of health expenditures on the total number of health institutions and the number of patients per physician were also analyzed. Conclusion: As a result, as health expenditures increase, the number of health institutions and the number of patients per physician increased. This means that there is an improvement in access to health services.

Amaç: Çalışmanın amacı, Türkiye'de sağlık harcamalarının bileşenlerini ve bunların toplam sağlık harcamaları üzerindeki etkilerini tespit etmek ve sağlık harcamalarının sağlık hizmetlerine erişim üzerindeki etkilerini incelemektir. Gereç ve Yöntem: Bu çalışmada, Türkiye'deki sağlık harcamaları 1999-2024 dönemi için Türkiye İstatistik Kurumu (TÜİK) verileri kullanılarak analiz edilmiştir. Analizler E-Views 12.0 programı ile gerçekleştirilmiş ve Birim Kök Testi, Granger Nedensellik ve Regresyon analizlerini içermiştir. Bulgular: Çalışmanın sonuçları, sağlık harcamalarının farklı bileşenlerinin toplam sağlık harcamaları üzerindeki etkilerini ortaya koymuştur. Cari sağlık harcamaları, hastane harcamaları ve diğer tıbbi malzeme harcamaları toplam sağlık harcamaları üzerinde önemli etkilere sahiptir. Ayrıca, sağlık harcamalarının toplam sağlık kurumu sayısı ve hekim başına düşen hasta sayısı üzerindeki etkileri de analiz edilmiştir. Sonuç: Sonuç olarak, sağlık harcamaları arttıkça sağlık kurumu sayısı ve hekim başına düşen hasta sayısı artmaktadır. Bu da sağlık hizmetlerine erişimde bir iyileşme olduğu anlamına gelmektedir.
Türkiye’de 1999-2024 Yılları Arasındaki Sağlık Harcamaları Dinamikleri ve Sağlık Sistemi Üzerindeki Etkileri
Keywords: Health Services and Systems (Other); Sağlık Hizmetleri ve Sistemleri (Diğer)